A new phenomenon of compressive strain recovery in gelatin-silica aerogel composites with SDS - Sachithanadam, Mahesh (2014)
Silica aerogels are nano-structured, highly porous solids with extremely low density but fragile and brittleness. To enhance the applicability of aeorgels, gelatin-silica aerogel (GSA) composite blocks were produced by mixing the hydrophobic aerogel-granules in a gelatin-SDS (sodium dodecyl sulfate) foamed-solution by frothing method. Gelatin essentially acts as binder whereas SDS enhances the foaming capacity of the mixture to the overall binding of the aerogels. The characteristics of these blocks depend on fabrication process and the gelatin-SDS composition. Especially, the strain recovery exhibited after compression is an unusual phenomenon observed with brittle silica aerogels. This paper discusses the effects of SDS on the density and the strain recovery of GSA composites. The fabrication process is explained; compression testing of these blocks is presented and associated strain recovery observed upon unloading is studied. The process variables such amount of gelatin/aerogel/SDS mix; compressive strain; and strain rates were analysed through Analysis of Variance (ANOVA). An empirical model that relates these variables to achieve the optimal strain recovery is established. In addition, the rule of mixture model with a correction factor was developed to estimate the densities of GSA-SDS composites. These composites can be used for heat protection, sound barrier, impact-resistance and shock-absorption.